INNOVATION OF MANAJEMENT IN IMPROVING ISLAMIC EDUCATION LEARNING QUALITY AT MAN 2 MODEL MEDAN - Fachruddin Azmi; Syafaruddin Syafaruddin; Khairuddin Khairuddin (JURNAL TARBIYAH, 2020)
This study is aimed to determine management innovation as an effort to improve the quality of learning Islamic religious education at Madrasah Aliyah Negeri (MAN) 2 Medan Model. The formulation of this study is focused on examining the aspects of planning, implementation, monitoring and evaluation implemented by the madrasah as an effort to improve the quality of Islamic Education learning. A qualitative was used as research approach. The data was obtained through interviews, observation, and documentation. Data analysis was analyzed through data reduction, data presentation, and data verification. The results of this study indicate that management innovation as an effort to improve the quality of Islamic education learning in MAN 2 Model Medan was carried out well. This is indicated by the ongoing learning activities in accordance with 4 aspects of the management function, they are: (1) planning which was carried out through annual meetings (deliberations) in determining strategic programs and activities and conceptualizing through lesson plan accompanied by varied media and methods; (2) implementation that is implemented based on lesson plan, added with extracurricular activities that were integrated with Islamic Education learning in the classroom, (3) internal supervision by the principal of madrasah to subordinates, added to providing guidance and counseling, and equipped with security by security staffs, and ( 4) learning evaluation was carried out by implementing routine and programmed tests, where evaluation is not only based on numbers, it coupled with an evaluation of students' religious experience in their respective environments.